Experiências de um lirismo agreste: o relato de identidades femininas, em As mulheres de Tijucopapo, de Marilene Felinto - Silva, Maria Emília Martins da (2012)
This thesis regards the reading of the novel The Women of Tijucopapo (2004), by Marilene Felinto, with emphasis on the reading of the relationships between the polyphonic othernesses and the protagonist -Risia- in three stages of the narrative (the child, the adult, and the mythical) in a discursive tangle. During the analysis process, the following primary hypotheses were elected: the non-place of the past (real or mythical) takes the durative present via memory; the memories provides a present constructive relationship placing the experience concerned with the enunciative subject in its singularity; a fictional temporal game of othernesses, which is articulated by the account of the pronominal triad I-SHE-THEY, emerges in the narrative. This paper was founded through three chapters starting from Mikhail Bakhtin s reflections and his concept of dialogism applied to the treatment of polysemy of the first-person narrator s poetic dialogs; Henri Bergson s supports the memorialist narrative in trancending history, as invented or fictional language production; and Giorgio Agamben s arguments childhood and contemporaneity themes, fundamental axis of transgressive enunciation in contemporary novels. The achieved results highlight that: by language experience of memorialist narratives, on the threshold of autobiographical, the discursive identities or dissonant subjects, and the split female first-person narrator builds a temporal flow of the narrative reconstruction among present, past and future. As the narrative unfolds, spacialities receive new poetic tenses through epic narration and, thereby, marking the novel genre on the origin of imagery recalled by the I and, set in dialogic relation by its univocal female othernesses: SHE/ THEY